2009
DOI: 10.1590/s1677-54492009000400009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre tratamento endovascular e cirurgia convencional na correção eletiva de aneurisma de aorta abdominal: revisão bibliográfica

Abstract: O tratamento eletivo do aneurisma de aorta abdominal é recomendado pela alta morbiletalidade decorrente da eventual ruptura. O objetivo deste trabalho foi comparar o reparo endovascular eletivo com a cirurgia aberta e avaliar as mortalidades hospitalar e perioperatória, em 1 ano, por todas as causas e relacionadas ao aneurisma, a permanência hospitalar, as complicações, as taxas de sobrevida, conversão e reintervenção, a durabilidade do enxerto, o custo-benefício e a relação desses dados com o treinamento da e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…The prevalence of AAA was 0.6% for 10 A diagnosis of AAA was more frequent among male patients (71.4%), in agreement with the literature. [1][2][3][4][5][6][7][8][9]17,22,[30][31][32] The mean diameter of the AAAs was 4 cm (range: 3.1 cm to 6.9 cm), which is similar to two other Brazilian studies, which found mean diameters of 3.9 cm 9 and 3.5 cm. 16 Elective treatment of AAAs is recommended when their diameter reaches 5.5 cm.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The prevalence of AAA was 0.6% for 10 A diagnosis of AAA was more frequent among male patients (71.4%), in agreement with the literature. [1][2][3][4][5][6][7][8][9]17,22,[30][31][32] The mean diameter of the AAAs was 4 cm (range: 3.1 cm to 6.9 cm), which is similar to two other Brazilian studies, which found mean diameters of 3.9 cm 9 and 3.5 cm. 16 Elective treatment of AAAs is recommended when their diameter reaches 5.5 cm.…”
Section: Discussionsupporting
confidence: 84%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]22,23,[30][31][32] While the 60.6% of the sample were CTs of female patients, there was a predominance (although not a statistically significant difference) of diagnoses among males [15 (60%) men and 10 (40%) women].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations